2008
DOI: 10.1002/jssc.200800336
|View full text |Cite
|
Sign up to set email alerts
|

CE determination of quinolones in the presence of bovine serum albumin

Abstract: This article describes the influence of bovine serum albumin (BSA) as an additive on the capillary electrophoresis-potential gradient determination of five quinolones, enoxacin, norfloxacin, ofloxacin, fleroxacin, and pazufloxacin. With 10 mg/L of BSA present in the buffer of 30 mM Tris and 3 mM phosphoric acid at pH 9, the detection limits of the five quinolones were in the range of 0.24-0.68 mg/L, i. e. 5.8-16.5-fold lower than those obtained with the buffer devoid of BSA, and the analysis time was shortened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Consequently, a number of novel CE developments are aimed at improving sensitivity in the detection of these substances by different means. For instance, the analysis of fluoroquinolones (FQs) has been investigated using different detection schemes, sample preconcentration and stacking methods 104–110. Recently, the detection of five quinolones, namely, enoxacin, norfloxacin, ofloxacin, fleroxacin and pazufloxacin has been approached by CE using potential gradient detection (PGD) in fortified milk samples 104.…”
Section: Toxins Contaminants Pesticides and Residuesmentioning
confidence: 99%
“…Consequently, a number of novel CE developments are aimed at improving sensitivity in the detection of these substances by different means. For instance, the analysis of fluoroquinolones (FQs) has been investigated using different detection schemes, sample preconcentration and stacking methods 104–110. Recently, the detection of five quinolones, namely, enoxacin, norfloxacin, ofloxacin, fleroxacin and pazufloxacin has been approached by CE using potential gradient detection (PGD) in fortified milk samples 104.…”
Section: Toxins Contaminants Pesticides and Residuesmentioning
confidence: 99%
“…The methods for determination of PAZU comprise both HPLC [ 26 , 27 , 49 ] and CE technique [ 50 52 ]. The analysed matrices were pharmaceutical formulation (tablets), milk [ 50 ], and biological fluids, i.e., serum, plasma, urine, muscle homogenate, saliva, gingiva, and crevicular fluid [ 26 , 27 , 49 , 51 , 52 ]. The applied columns in HPLC were C18 [ 27 , 49 ] and C8 [ 26 ].…”
Section: Third Generation Fluoroquinolonesmentioning
confidence: 99%
“…The other contents were 0.5% phosphoric acid containing 1% of TEA [ 49 ] or 1% TEA solution [ 26 ] or 0.1% formic acid at pH 3.0 adjusted with TEA [ 27 ]. CE separation was performed at room temperature, and the background electrolyte (BGE) was an aqueous solution of TRIS and phosphoric acid [ 50 , 51 ]. The other additives were phosphates and β-cyclodextrines [ 52 ].…”
Section: Third Generation Fluoroquinolonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that the presence of BSA suppressed the adsorption of quinolones in the inner wall of the capillary and increased the EOF rate. Finally, the method was applied to the determination of fluoroquinolones in spiked samples obtaining recoveries in the range from 81.9 to 104.3% 37.…”
Section: Quinolones and Fluoroquinolonesmentioning
confidence: 99%